2016
DOI: 10.1111/jog.13084
|View full text |Cite|
|
Sign up to set email alerts
|

Complete response to paclitaxel, ifosfamide, and cisplatin therapy in a case of ovarian ependymoma

Abstract: There are many reports on paclitaxel, ifosfamide, and cisplatin (TIP) therapy, following standard bleomycin, etoposide, and cisplatin (BEP) therapy, for salvage treatment of testicular malignant germ cell tumors, but there are no reports on its use for ovarian malignant tumors. We report here that a patient with primary ependymoma of the ovary, who was resistant to BEP therapy, achieved a complete response to a combined therapy, including TIP therapy as the second-line chemotherapy and surgery. This important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Hirahara et al reported a case of pure ovarian ependymoma which had undergone chemotherapy such as cisplatin, CAP (cisplatin/aclarubicin/cyclophosphamide), VAC (vincristine/dactinomycin/cyclophosphamide), EP (etoposide/cisplatin), and doxorubicin/mitomycin C [15]. Hino et al reported a case of ovarian ependymoma failing BEP (bleomycin/etoposide/cisplatin) with complete response after treatment with TIP (paclitaxel/ifosfamide/cisplatin) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hirahara et al reported a case of pure ovarian ependymoma which had undergone chemotherapy such as cisplatin, CAP (cisplatin/aclarubicin/cyclophosphamide), VAC (vincristine/dactinomycin/cyclophosphamide), EP (etoposide/cisplatin), and doxorubicin/mitomycin C [15]. Hino et al reported a case of ovarian ependymoma failing BEP (bleomycin/etoposide/cisplatin) with complete response after treatment with TIP (paclitaxel/ifosfamide/cisplatin) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in the literature, the treatment of ovarian ependymoma is primarily based on the treatment of malignant germ cell tumours, including surgical debulking followed by adjuvant chemotherapy. The traditional first-line chemotherapy regimen consisting of bleomycin, etoposide and cisplatin(BEP) for germ cell tumours is effective for ovarian ependymomas [ 1 , 5 ]. Moreover, Hino et al have suggested that paciltaxel, ifosfamide, and cisplatin therapy can be used as an effective second-line therapy for ovarian ependymomas resistant to BEP therapy [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of paclitaxel, ifosfamide, and cisplatin (TIP) has also been identified as another chemotherapeutic option in the setting of BEP resistant disease as described in a recent case report (Hino et al, 2016). This modality has achieved success in salvage treatment of testicular malignant germ cell tumors and its use has recently been extrapolated to ovarian ependymoma.…”
Section: Discussionmentioning
confidence: 99%